KLASIFIKASI SENTIMEN PEMBELI BERDASARKAN LAYANAN SMS “SUARA KONSUMEN” TERHADAP PRODUK MENGGUNAKAN METODE K-NN - David Addiwijaya Hanz; Budi Susanto; Lukas Chrisantyo (Universitas Kristen Duta Wacana, 2015)
Limited number of characters in an SMS causes the use of words and the structure of solid and compact but obviously become very important in presenting the content and purpose of the sender of the SMS. This research studied how the use of SMS classify structures and limited words to get the sentiment of an SMS service